The Relationship Between Knowledge and Digital Utilization in the Culinary Sector: An SMEs Perspective - Ayu Hasra Nurfaiza; Muh. Rayhan Akmal Nazhmi; Andi Naila Quin Azisah Alisyahbana; Matthew Olufemi Adio (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2024)
This study discusses the influence of knowledge of MSME actors in the use of digitalization in the culinary industry in Makassar City. This study aims to determine and analyze how socialization and interaction affect the knowledge of MSME actors and the extent to which this knowledge affects the use of digitalization in marketing. This research uses a quantitative approach and survey as a data collection method. The results showed that MSME players' knowledge of digitalization affects the utilization of digitalization in marketing, and socialization and interaction affect the knowledge of MSME players. This study hopes to contribute to the theoretical understanding of the factors affecting MSMEs and provide a basis for formulating more appropriate and effective strategies for MSME development.